Analysis of the Implementation of Good Governance Principles in the Framework of Accelerating Bureaucratic Reform in the Gayo Lues Regency Government - Yarman, Subdi; Abu Bakar, Muhammad Bin; Rulinawaty, Rulinawaty (Riwayat: Educational Journal of History and Humanities, 2024)
The acceleration of bureaucratic reform of the Gayo Lues government wants fundamental changes in the implementation of a more transparent government that can be analysed through the application of good governance. The purpose of this study is to determine the results of the analysis of the application of good governance principles in the provision of bureaucratic services in the Gayo Lues Regency Government. This research method uses a qualitative-descriptive approach. Data collection techniques by means of field observation, interviews and relevant literature studies. The analysis carried out, this study concluded that; first, the application of good governance principles such as public participation, transparency and accountability in the implementation of the Gayo Lues Regency Government, in general, has been implemented well, tends to be formalistic and administrative, has not fully focused on achieving the targets of bureaucratic reform itself. The application of good governance principles in public services is still carried out partially and has not been integrated, so it has not leveraged improvements and services. In addition, the planning for the development of apparatus competencies has not been carried out comprehensively, there has been no talent mapping as a basis for placing employees in a position. The implementation of good governance principles has had a less significant impact on development and community welfare. Gayo Lues Regency has not been able to get out of more substantive problems such as poverty, slow economic empowerment of the community, low quality of education, low level of public health, and low development of human resources. The problems faced by the Gayo Lues Regency government in implementing the principles of good governance in public services are very complex and involve many dimensions. Efforts to improve the performance of the apparatus and services require holistic government intervention and of course public support is also very important. This problem is the most urgent and must be resolved immediately